2015
DOI: 10.1097/qad.0000000000000724
|View full text |Cite
|
Sign up to set email alerts
|

Hidden from health

Abstract: Objective Substantial country-level variation exists in prejudiced attitudes towards male homosexuality and in the extent to which countries promote the unequal treatment of MSM through discriminatory laws. The impact and underlying mechanisms of country-level stigma on odds of diagnosed HIV, sexual opportunities, and experience of HIV-prevention services, needs and behaviours have rarely been examined, however. Design Data come from the European MSM Internet Survey (EMIS), which was administered between Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
104
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 269 publications
(107 citation statements)
references
References 31 publications
1
104
2
Order By: Relevance
“…27 Third, we used a measure of anti-immigrant attitudes to capture structural variation in anti-immigrant stigma across receiving countries, whereas we used legislation to represent anti-gay structural stigma, because population-based studies of attitudes toward sexual minorities do not exist for all countries. However, the fact that anti-gay legislation in Europe is strongly correlated with anti-gay attitudes in those countries 2 strengthens the validity of our measurement approach. Fourth, because we only examined national forms of structural stigma, future research should consider the role of local laws that might reinforce or protect against structural stigma at the country level.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…27 Third, we used a measure of anti-immigrant attitudes to capture structural variation in anti-immigrant stigma across receiving countries, whereas we used legislation to represent anti-gay structural stigma, because population-based studies of attitudes toward sexual minorities do not exist for all countries. However, the fact that anti-gay legislation in Europe is strongly correlated with anti-gay attitudes in those countries 2 strengthens the validity of our measurement approach. Fourth, because we only examined national forms of structural stigma, future research should consider the role of local laws that might reinforce or protect against structural stigma at the country level.…”
Section: Discussionmentioning
confidence: 59%
“…3,25,26 Further, the mechanisms linking structural stigma to MSM’s HIV risks remain largely unknown, although emerging research suggests MSM living in more homonegative countries report more sexual orientation concealment, which predicts some HIV-related risks. 2 Future research might explore additional mechanisms linking early and current structural stigma to HIV-prevention outcomes, including learned behavioral responses to stress, lack of access to HIV-prevention knowledge during sensitive developmental stages, and perceptions of stigma in healthcare and other more proximal institutions. 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, several personal and environmental factors might moderate associations between outness and mental health, including structural stigma, cohort, socioeconomic status, race/ethnicity, family support, and religiosity. While investigating these contextual influences is beyond the scope of the present investigation, recent research is beginning to reveal the importance of considering the influence of such factors on sexual orientation concealment and health (e.g., McGarrity & Huebner, 2014; Pachankis et al, 2015). An intersectionality perspective could usefully extend this research beyond statistical tests of interaction to capture the nuanced meaning and mental health consequences of possessing multiple stigmatized identities, both concealable and visible, in contexts of inequality across the life course (Carbado, Crenshaw, Mays, & Tomlinson, 2013; Clark & McCall, 2013; Cole, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MSM remain a vulnerable population for HIV-infection in Latin America (24) with a 14·2% estimated point prevalence of HIV-infection in Brazil (25) that drastically contrasts with the 0·6% HIV-infection prevalence in the Brazilian general population (11). Beyond increased risk of HIV-infection, MSM are subject to stigma that operates at several levels including internalized, interpersonal and structural, all of which stand as barriers to access and utilization of HIV prevention and treatment services (26, 27). Though not HIV-specific, a recent systematic review found that prejudice against nonheterosexual orientation is prevalent in diverse regions of Brazil (28).…”
Section: Discussionmentioning
confidence: 99%